Enhanced transdermal permeability of Terbinafine through novel nanoemulgel formulation; Development, in vitro and in vivo characterization - Maha E. Elmataeeshy; Magda S. Sokar; Mohammed Bahey-; Dalia S. Shaker (SpringerOpen, 2018)
Terbinafine Hcl (TB) is a poorly water soluble antifungal drug. Topical nanoemulsion based gel containing TB was prepared with a view to improve its solubility and antifungal activity. In preparation of the nanoemulsion (NE), excipients were selected based on the solubility study. Peceol was optimized as the oil phase. Tween 80 and propanol were optimized as the surfactant and co-solvent respectively, and were mixed (Smix) in different weight ratios (1:1, 1:2, 1:3, 1:4, 4:1, 3:1 and 2:1, respectively). Pseudoternary phase diagrams were developed and Pecol and Smix were mixed in different weight ratios ranging from 1:9 to 9:1. Based on the NE region of each diagram, the formulae were selected. The formulated nanoemulsions were characterized and evaluated for in vitro drug release and thermodynamic stability. The optimum nanoemulsion formulae containing 10 or 15% w/w oil, 45% w/w Smix (1:2/1:3) and 45-40% w/w aqueous phase) were incorporated into Carbopol 940 gel bases forming three different TB nanoemulsion based emulgel formulae (F1-F3) which were examined for ex vivo drug permeation and in vivo antifungal activity compared to the marketed product; Lamisil® emulgel. The results showed that TB skin permeation from all the prepared nanoemulsion based gel formulae was significantly (p < 0.05) improved in relation to the commercial emulgel. F3 exhibited a superior in vivo antifungal activity over the marketed emulgel for the treatment of Candida infection. Keywords: Terbinafine nanoemulsion, Pseudoternary phase diagrams, Permeation study